Wer ist der beste Formel 1 Fahrer? Eine ökonometrische Talentbewertung - David Stadelmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Who is the best formula 1 driver? Until today it was impossible to answer this question because the observable performance of a driver depends both on his talent and the quality of his cars. In this paper we for the first time separate driver talent from car quality by econometrically analyzing data for 57 years of Formula 1 racing. Our estimates also control for the number of drivers finishing, technical breakdowns and many other variables that influence race results. While Michael Schumacher is often believed to be the best driver, he is overtaken by Juan Manuel Fangio and Jim Clark.
Keywords: 330